2018
DOI: 10.1186/s12889-018-5593-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between parent feeding behaviors and parent and child characteristics in Brazilian preschoolers: a cross-sectional study

Abstract: BackgroundEating habits formed in early childhood are influenced by parental feeding behaviors, warranting investigation of predictors and correlates of parent feeding. We aimed to describe relationships between parental feeding practices and parent and child characteristics in a sample of Brazilian preschoolers.MethodsFour hundred and two parents of preschoolers enrolled in private schools of São Paulo and Campinas, Brazil, completed a Brazilian version of the Comprehensive Feeding Practices Questionnaire, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 44 publications
2
38
1
2
Order By: Relevance
“…Another possible explanation is that important factors related to maternal feeding practices might have been missed [50]. Compared to mothers recruited in other studies [17,25,31], mothers in our study showed a relatively low level of weight concern. Additionally, the correlations between weight concern and maternal feeding practices were weak.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Another possible explanation is that important factors related to maternal feeding practices might have been missed [50]. Compared to mothers recruited in other studies [17,25,31], mothers in our study showed a relatively low level of weight concern. Additionally, the correlations between weight concern and maternal feeding practices were weak.…”
Section: Discussioncontrasting
confidence: 55%
“…Many studies have identified factors related to non-responsive feeding practices [13][14][15][16][17]. Among these factors, child weight has been an important factor [13, [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before effective interventions can be designed, formative research is needed to identify the key predictors of parents' decision making for healthy feeding practices. Previous studies that have investigated parents' feeding behaviours of preschoolers mostly focused on associating parent characteristics to parents' feeding behaviours (e.g., Kröller & Warschburger, 2008;McCurdy, Gorman, Kisler, & Metallinos-Katsaras, 2014;McCurdy, Gorman, & Metallinos-Katsaras, 2010;Warkentin, Mais, de Oliveira, Carnell, & de Aguiar CarrazedoTaddei, 2018). These studies found that parents' education, BMI and mental health (i.e., maternal depression) were associated with healthy feeding practices in preschoolers.…”
Section: Introductionmentioning
confidence: 99%